The confrontation of James Taylor Junior (Leader of the exclusive Brethren) and his supporters ; vol. 1 - Calvey, Hubert (Lancashire, UK H. Calvey, 1967)
Contents : v. 1 : Being ten letters addressed to James Taylor Jr., in 1965 on "Righteousness and truth and responsibility".
Keywords: Brethren movement -- Exclusive Brethren -- controversies